Design of Symmetrical Beam Triple-Aperture Waveguide Antenna for Primary Feed of Reflector - Kanawat Nuangwongsa; Chuwong Phongcharoenpanich (My University, 2016)
This research presents a triple-aperture waveguide antenna as the primary feed of parabolic reflectors. The proposed antenna is able to rectify the asymmetry and also achieve a symmetrical unidirectional beam through the application of two parasitic coupling apertures. The design of the antenna is that of a rectangular waveguide (radiating aperture) vertically jointed to the two coupling apertures of the same measurement widthwise (i.e., one stacked on top and the other underneath) to achieve the symmetrical beam. The rectangular waveguide is 97.60 mm and 46.80 mm in width (a) and height (b), respectively, to propagate the WLAN frequency band of 2.412–2.484 GHz. Simulations were carried out to determine the optimal antenna parameters and an antenna prototype was subsequently fabricated and tested. The simulated beamwidths in theE- andH-planes at-3 dB were equally 67° (i.e., 67° for both theE- andH-planes) and at-10 dB also equally 137°, while the measured results at-3 dB were equally 65° and at-10 dB equally 135°. The simulation and measured results are thus in good agreement. The simulated and measured antenna gains are, respectively, 8.25 dBi and 9.17 dBi. The findings validate the applicability of the antenna as the prime feed for rotationally symmetric parabolic reflectors.
Keywords: Waveguide; Numerical aperture; Microwave Engineering and Waveguides